Tema Hukum Islam - Hesti Ratna Murni; Relit Nur Edi; Hendriyadi (CV Rewang Rencang, 2025)
The main focus of this research is to analyze the implementation of law enforcement against the practice of vote buying in elections and to examine it from the perspective of siyasah tanfidziyyah (executive political governance). This study employs a qualitative approach with a juridical-empirical research method, in which data were collected through interviews, observations, and documentation conducted in Ulu Danau Village, Sindang Danau District, South OKU Regency. The findings indicate that vote-buying practices remain prevalent during elections due to weak supervision and the low level of public legal awareness. Although Article 515 of Law Number 7 of 2017 provides for criminal sanctions, its implementation has not been optimal because of difficulties in proving violations and the lack of firmness among law enforcement officers. From the perspective of siyasah tanfidziyyah, vote buying constitutes an act that contradicts the principles of justice, trustworthiness, and public welfare. Therefore, law enforcement should not only be carried out juridically but also through strengthening the moral and spiritual values of society to realize fair and integrity-based elections. Keywords: Law enforcement, Money politics, Election, Siyasah Tanfidziyyah